Cyborg Cinema and Contemporary Subjectivity - Short, S. author. aut Link
XVI, 251 p.
Keywords: This book breaks new ground in providing an in-depth critical assessment of cyborg cinema, arguing that it remains one of the most intriguing and provocative cycles to have emerged in contemporary screen culture. Tracing the cinematic cyborg's transition over the last two decades and evaluating the theoretical significance attributed to this figure, it asks what relevance the cyborg continues to have in terms of understanding human identity, our relationship to technology, and to one another.